Galanin regulates the postnatal survival of a subset of basal forebrain cholinergic neurons - O'Meara, Gillian (The National Academy of Sciences, 2000)
The neuropeptide galanin colocalizes with choline acetyltransferase, the synthetic enzyme for acetylcholine, in a subset of cholinergic neurons in the basal forebrain of rodents. Chronic intracerebroventricular infusion of nerve growth factor induces a 3- to 4-fold increase in galanin gene expression in these neurons. Here we report the loss of a third of cholinergic neurons in the medial septum and vertical limb diagonal band of the basal forebrain of adult mice carrying a targeted loss-of-function mutation in the galanin gene. These deficits are associated with a 2-fold increase in the number of apoptotic cells in the forebrain at postnatal day seven. This loss is associated with marked age-dependent deficits in stimulated acetylcholine release, performance in the Morris water maze, and induction of long-term potentiation in the CA1 region of the hippocampus. These data provide unexpected evidence that galanin plays a trophic role to regulate the development and function of a subset of septohippocampal cholinergic neurons.